Mathematical modeling of plasma thruster device thermal processes - V. V. Shalay; V. I. Gorbunkov; I. V. Kolganov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
A mathematical model of thermodynamic processes occurring in the arcjet thruster device with using argon for arcjet working process carring out. A comparative analysis of the results of experimental data with theoretical data has been carried out. The purpose of the study is to develop a mathematical model of thermodynamic processes in the arcjet thruster device and simulate the interaction of argon with arc discharge plasma. The comparative analysis of the calculated parameters, thanks to the proximity of electron temperature values with the previously experimentally obtained under the static state in the arcjet thruster device, confirms the reliability of the presented mathematical model of plasma processes and the need for its improvement.